2007
DOI: 10.1029/2007ja012560
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and solar cycle variability in F‐region vertical plasma drifts over Ouagadougou

Abstract: [1] F-region vertical drifts were made using ionosonde for the Africa equatorial station Ouagadougou (12°N, 1.5°W; 5.9°N dip) from 3 a of data during January 1987 to December 1989 for solar cycle minimum, medium, and maximum conditions (F 10.7 = 85, 141, and 214, respectively) under geomagnetic quiet-time. The variations are found to be dominated by the characteristics morning peak and evening prereversal enhancement (PRE) velocities. Seasonal and solar cycle effects are prominent near the dusk sector with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…Using h m F 2 method, Oyekola et al . [] have also studied the vertical drifts over African region by using ionosonde. They showed that their PRE drift variations are in good agreement with solar flux variations.…”
Section: Discussionmentioning
confidence: 99%
“…Using h m F 2 method, Oyekola et al . [] have also studied the vertical drifts over African region by using ionosonde. They showed that their PRE drift variations are in good agreement with solar flux variations.…”
Section: Discussionmentioning
confidence: 99%
“…A likely cause of substantial variability of F region vertical ion drifts may perhaps are due to the trans‐equatorial wind intensity effects since the two stations (Ibadan and Ouagadougou) are not located exactly at the dip equator. A number of theoretical, model calculations, and observational evidence have shown that transequatorial magnetic meridional wind intensity play a critical role in the variability of ion drifts, especially near the prereversal hours [e.g., Maruyama , 1988; Mendillo et al , 1992; Abdu et al , 2006; Su et al , 2007; Oyekola et al , 2007]. Moreover, Mendillo et al [2002] showed that the F 2 layer variability appears to be related more to variations in winds than to variations of thermospheric composition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus in the post sunset hours F layer moves upward rapidly and then comes down due to decay of this PRE associated eastward electric field. It is noticed that PRE varies considerably from day‐to‐day and it also depends on season, solar flux and longitude [ Abdu et al , 1981; Batista et al , 1986; Hari and Krishna Murthy , 1995; Fejer and Scherliess , 2001; Oyekola et al , 2007]. As a result the post sunset height of F layer varies considerably from day to day for magnetically quiet periods, which gets reflected in the monthly quiet time pattern of apparent base height of F layer h ′ F .…”
Section: Data Used and Quantitative Estimate Of Magnetic Activitymentioning
confidence: 99%